A Paulo Freire based education in favor of gender equality in contemporary Brazil (Práxis Educativa, 2021)
This study discusses the relationship between the democratic values-based Freire's education method and the discussions about gender inequality in Brazilian schools. In this concern, we asked ourselves about the role that discussions about gender and sexual diversity play in school and in the construction of a fairer and more equitable society, reflecting on the consequences of promoting interdictions in school education on themes fundamental to the balance of social forces. The study considers that the insertion of such theme at school contributes to the deconstruction of stereotypes, the promotion of mutual respect and the reduction of prejudices, developing a collective critical awareness capable of leading students to look at themselves and at each other as integral parts of the same social body, guiding new generations towards the ideal of equality within diversity.Keywords: Gender Inequality. Democratic education. Freirean pedagogy.